Board Meeting Effectiveness and Bank Performance: Evidence from Sub-Saharan Africa - Lawrence Asare Boadi; Philomena Dadzie; Sampson Narteh-Yoe; James Ntiamoah Doku; Richard Takyi Opoku; Kofi Afriyie Nyamekye (International Journal of Economics and Financial Issues, 2023)
The main objective of the study was to evaluate the effectiveness and performance of board meetings at banks in sub-Saharan Africa. The study adopted a quantitative research design and collected secondary data from the annual reports of 33 banks in sub-Saharan Africa to cover the period 2011–2020. To achieve its research objective, the study employed the two-step GMM regression model to examine the relationship between board meeting effectiveness and bank performance. A positive and statistically significant correlation between the effectiveness of board meetings and the financial success of banks was discovered in this research. Our results suggest that improving the efficiency of board meetings can be a viable strategy for boosting bank performance, which has significant ramifications for bank governance in sub-Saharan Africa.